Supported Fe-Mn carbon fiber catalyst for catalyzing low-concentration VOCs (Volatile Organic Compounds) as well as preparation method and application thereof
Through the preparation method of load FE-Mn charcoal fiber catalyst, the high cost and thermal stability of existing catalysts in catalytic low-concentration VOCs are solved, and high-efficiency and stable VOCS degradation is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411483139.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing catalysts have high cost, poor thermal stability and complex industrial applications when catalyzing low-concentration VOCs. The traditional activated carbon pretreatment methods are complex, and the adsorption capacity is fixed and regeneration is difficult.
The load-load FE-Mn charcoal fiber catalyst is used, and the activated carbon fiber powder is mixed with manganese salt and iron salt to regulate the pH value to perform aging, filtering, washing, drying, and roasting. Activation and stability catalyst.
The efficient degradation of low -concentration VOCS has been achieved, the cost of catalysts is low, and it has excellent catalytic performance and stability. It is suitable for the industrial environment of no tissue emissions of pollutants.
Smart Images

Figure CN119346129A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysis, and in particular to a supported Fe-Mn carbon fiber catalyst for catalyzing low-concentration VOCs, a preparation method and an application thereof. Technical Background
[0002] Among many treatment methods, the most widely used and effective method is catalytic combustion, the core of which is to develop efficient and stable catalysts. Supported catalysts are often used in industrial applications. Suitable carriers are conducive to the dispersion of active components and improve catalytic activity. Activated carbon fiber is considered to be an ideal carrier because of its excellent performance. Patent CN 108993533 B discloses a method for preparing a supported precious metal catalyst, which is obtained by loading the active component platinum on a copper-tin composite oxide carrier, and has a good degradation effect on VOCs at low temperature. Patent CN 111135840 B discloses a method for preparing a supported single-atom dispersed precious metal catalyst, and the obtained catalyst has a high metal dispersion. Precious metal catalysts have good catalytic activity, but precious metal catalysts generally have problems such as high price and poor thermal stability, which limit their large-scale industrial application; while transition metal oxide catalysts have the advantages of variable valence, low price, good thermal stability, etc., and are a hot spot in the field of catalytic combustion research. Among them, MnOx is considered to be an excellent catalyst active component because of its multivalent chemical structure and efficient catalytic activity. Adding other metals to manganese oxide can improve the performance of the catalyst. Xiangtan University has publicly invented a Cu-MnO 2 Preparation method of catalyst (CN 116212889 A), Cu-MnO obtained by one-step solvothermal method 2 The catalyst can effectively remove high concentrations of VOCs. Huazhong University of Science and Technology has disclosed a method for preparing a Ce-Mn catalyst (CN 109701547B). The catalyst is synthesized by a two-step method. x Mn 8 O 16 The physical phase Mn-Ce catalyst has good selectivity in the treatment of methane waste gas. Cu-Mn, Co-Mn and Ce-Mn oxide catalysts have been widely studied in the catalytic oxidation of VOCs, but there are few reports on improving the activity of catalysts through the interaction between Fe-Mn. Jinan University disclosed a zero-valent iron-manganese composite modified activated carbon and its preparation method and application (CN 112934176 A). The modified activated carbon can efficiently treat a variety of water bodies through adsorption, but the activated carbon pretreatment method is complicated, and there are problems such as fixed adsorption capacity and difficulty in regeneration, which is not conducive to industrial application.
[0003] In actual catalytic applications, the pollutant concentrations in most factories are low, the emissions are large, the emissions are unstable and unorganized. Therefore, it is of great significance to develop a highly active supported carbon fiber catalyst and apply it to catalysis in low-concentration pollutant environments. Summary of the invention
[0004] The purpose of the present invention is to provide a supported Fe-Mn carbon fiber catalyst for catalyzing low-concentration VOCs, a preparation method and an application thereof. The catalyst preparation method is simple, the raw materials are cheap, the catalyst has excellent catalytic performance and stability, has a high degradation rate for low-concentration VOCs, and is suitable for industries with unorganized pollutant emissions.
[0005] A method for preparing a supported activated carbon fiber catalyst for catalyzing low-concentration VOCs, characterized in that the preparation method comprises the following steps:
[0006] (1) washing and drying the carrier activated carbon fiber powder, adding the dried carbon fiber powder to a metal precursor solution and mixing to obtain a mixed solution; the metal precursor is a manganese salt and an iron salt;
[0007] (2) adjusting the pH value of the mixed solution to 7-10, and then aging, filtering, washing, drying and calcining the mixed solution in sequence to obtain a catalyst precursor;
[0008] (3) The catalyst precursor and aluminum gel are mixed evenly, bonded and formed by acidification, and then dried and calcined in sequence to obtain a supported Fe-Mn carbon fiber catalyst.
[0009] In the above method, in step 1), the activated carbon fiber powder is dried at a temperature of 90-120° C. and for a drying time of 8-12 hours.
[0010] Preferably, the activated carbon fiber powder is dried at a temperature of 100-110° C. and for a drying time of 8-10 h.
[0011] In the above method, the aging temperature in step (2) is 15-25°C, preferably 20-25°C, and the aging time is 1-5h, preferably 3-5h; the drying temperature is 90-120°C, preferably 100-110°C; the drying time is 8-12h, preferably 8-10h; the calcination temperature is 400-600°C, preferably 400-500°C; and the calcination time is 1-5h, preferably 4-5h.
[0012] In the above method, in step 3), the aluminum gel is pseudo-boehmite, aluminum dihydrogen phosphate or aluminum hydroxide sol, and the mass ratio of aluminum gel to catalyst precursor is 20-50:100, preferably 30-50:100; the acid used for acidification is nitric acid, acetic acid, phosphoric acid, the mass concentration of the acid is 3-10%, preferably 4-8%, and the ratio of the amount of acid added to the catalyst precursor mixture is 30-100ml:100g.
[0013] In the above method, in step 3), the drying temperature is 90-120° C., and the drying time is 8-12 hours; the roasting temperature is 400-600° C., and the roasting time is 3-5 hours.
[0014] A supported activated carbon fiber catalyst for catalyzing low-concentration VOCs is prepared by the above method.
[0015] In the above-mentioned supported activated carbon fiber catalyst for catalyzing low-concentration VOCs, the mass loading amount of metal oxide is 5-25% based on the activated carbon fiber carrier; the iron salt and manganese salt are any one or more of nitrate, sulfate, and chloride, and the molar ratio of Fe:Mn element is (1-5):1.
[0016] Preferably, based on the activated carbon fiber carrier, the mass loading of the metal oxide is 15-25%.
[0017] In the technical solution of the present invention, the catalyst prepared by the above method is used to catalyze the degradation of VOCs at low concentrations.
[0018] Further: VOCs are aromatic, ester, and hydrocarbon compounds, and the low concentration is 400-600ppm.
[0019] Further: The carrier gas for the catalytic reaction is air, and the space velocity of the catalytic reaction is 10000-15000h -1 , the reaction temperature is 70-400℃.
[0020] The preparation method of the present invention is simple and easy to control, the raw materials and metal salts are cheap and easily available, the obtained catalyst has good controllability, high catalytic activity and stability, and is easy to realize industrial application. In the catalysis of low-concentration VOCs pollutants, it shows excellent catalytic activity and stability, is suitable for industries with large emissions, unstable emissions and unorganized emissions, and has broad application prospects and high economic benefits in the catalytic oxidation of VOCs. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 2 are the XRD patterns of Example 2, Example 4 and Example 5. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents the selected embodiments of the present invention.
[0023] Example 1
[0024] The viscose-based activated carbon fiber powder was washed with deionized water and dried at 90°C for 12h. The metal oxide loading was controlled to be 5%, the Fe:Mn molar ratio was 1:1, and the iron nitrate and manganese nitrate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 10, and then the mixed solution was aged at 25°C for 3h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 90°C for 12h and air-baked at 500°C for 4h to obtain a catalyst precursor. Aluminum dihydrogen phosphate was weighed and mixed evenly with the catalyst precursor in a mass ratio of 50:100. Then 3wt% acetic acid solution and the catalyst precursor mixture were added in a ratio of 100ml:100g, bonded and formed, dried at 90°C for 12h, and transferred to 500°C air for 4h to obtain a loaded Fe-Mn activated carbon fiber catalyst.
[0025] Example 2
[0026] The viscose-based activated carbon fiber powder was washed with deionized water and dried at 100°C for 10h. The metal oxide loading was controlled to be 20%, the Fe:Mn molar ratio was 1:1, and the iron nitrate and manganese nitrate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 7, and then the mixed solution was aged at 25°C for 3h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 100°C for 10h and air-baked at 500°C for 4h to obtain a catalyst precursor. Pseudo-boehmite was weighed and mixed evenly with the catalyst precursor in a mass ratio of 50:100. Then, 3wt% of acetic acid solution and the catalyst precursor mixture were added in a ratio of 100ml:100g, dried at 100°C for 10h, and then transferred to 500°C air for 4h to obtain a supported Fe-Mn activated carbon fiber catalyst. XRD characterization results show that in addition to the characteristic diffraction peaks of graphite observed in Example 2, Fe 2 O 3 and Mn 3 O4 The mixed valence is an important property of redox catalysis. 2 O 3 and Mn 3 O 4 The presence of crystals can promote the occurrence of lattice defects and the exposure of internal atoms, which is beneficial to the catalytic reaction.
[0027] Example 3
[0028] The viscose-based activated carbon fiber powder was washed with deionized water and dried at 100°C for 10h. The metal oxide loading was controlled to be 25%, the Fe:Mn molar ratio was 1:1, and the iron sulfate and manganese sulfate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixture was adjusted to 8, and then the mixed solution was aged at 25°C for 1h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 100°C for 10h and air-baked at 500°C for 1h to obtain a catalyst precursor. Pseudo-boehmite and catalyst precursor were weighed evenly at a mass ratio of 20:100. Then, 10wt% phosphoric acid solution and catalyst precursor mixture were added at a ratio of 30ml:100g, bonded and formed, dried at 100°C for 10h, and transferred to 500°C air for calcination for 3h to obtain a loaded Fe-Mn activated carbon fiber catalyst.
[0029] Example 4
[0030] The viscose-based activated carbon fiber powder was washed with deionized water and dried at 110°C for 8 hours. The metal oxide loading was controlled to be 20%, the Fe:Mn molar ratio was 3:1, and the iron nitrate and manganese nitrate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 7, and then the mixed solution was aged at 25°C for 3 hours, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 110°C for 8 hours and air-baked at 500°C for 4 hours to obtain a catalyst precursor. Pseudo-boehmite was weighed and mixed evenly with the catalyst precursor in a mass ratio of 50:100. Then, 3wt% nitric acid solution and the catalyst precursor mixture were added in a ratio of 100ml:100g, bonded and formed, and after drying at 110°C for 8 hours, transferred to 500°C air and calcined for 4 hours to obtain a loaded Fe-Mn activated carbon fiber catalyst. XRD characterization results show that Example 4 only shows Fe 2 O 3 The characteristic peaks of Mn oxides were not observed. This indicates that manganese oxides may exist in an amorphous state or in a highly dispersed state on the catalyst surface, which is beneficial to improving the catalytic activity.
[0031] Example 5
[0032] The viscose-based activated carbon fiber powder was washed with deionized water and dried at 120°C for 8h. The metal oxide loading was controlled to be 20%, the Fe:Mn molar ratio was 5:1, and the iron nitrate and manganese nitrate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 7, and then the mixed solution was aged at 25°C for 3h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 120°C for 8h and air-baked at 500°C for 5h to obtain a catalyst precursor. Aluminum dihydrogen phosphate was weighed and mixed evenly with the catalyst precursor in a mass ratio of 40:100. Then 3wt% acetic acid solution and the catalyst precursor mixture were added in a ratio of 100ml:100g, bonded and formed, dried at 120°C for 8h, and then transferred to 500°C air and calcined for 5h to obtain a loaded Fe-Mn activated carbon fiber catalyst. XRD characterization results show that Example 5 is the same as Example 4, only Fe 2 O 3 The characteristic peaks of Mn oxides were not observed.
[0033] Example 6
[0034] The polyacrylonitrile-based activated carbon fiber powder was washed with deionized water and dried at 100°C for 10h. The metal oxide loading was controlled to be 20%, the Fe:Mn molar ratio was 1:1, and the iron sulfate and manganese sulfate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 10, and then the mixed solution was aged at 15°C for 5h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 100°C for 10h and air-baked at 600°C for 4h to obtain a catalyst precursor. Aluminum hydroxide sol was weighed and mixed evenly with the catalyst precursor in a mass ratio of 50:100. Then, 5wt% nitric acid solution and the catalyst precursor mixture were added in a ratio of 50ml:100g, bonded and formed, dried at 100°C for 10h, and then transferred to 600°C air for 4h to obtain a loaded Fe-Mn activated carbon fiber catalyst.
[0035] Example 7
[0036] The polyacrylonitrile-based activated carbon fiber powder was washed with deionized water and dried at 100°C for 10h. The metal oxide loading was controlled to be 20%, the Fe:Mn molar ratio was 1:1, and the iron nitrate and manganese nitrate samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 7, and then the mixed solution was aged at 20°C for 3h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 100°C for 10h and air-baked at 400°C for 4h to obtain a catalyst precursor. Aluminum hydroxide sol was weighed and mixed evenly with the catalyst precursor in a mass ratio of 50:100. Then 3wt% nitric acid solution and the catalyst precursor mixture were added in a ratio of 100ml:100g, bonded and formed, dried at 100°C for 10h, and then transferred to 400°C air for 4h to obtain a loaded Fe-Mn activated carbon fiber catalyst.
[0037] Example 8
[0038] The viscose-based activated carbon fiber powder was washed with deionized water and dried at 100°C for 10h. The metal oxide loading was controlled to be 20%, the Fe:Mn molar ratio was 1:1, and the ferric chloride and manganese chloride samples were weighed and dissolved to obtain a metal precursor solution. The dried carbon fiber powder was added to the metal precursor solution and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 7, and then the mixed solution was aged at 25°C for 3h, washed three times with distilled water, and then solid-liquid separation was performed by suction filtration. The product was dried at 100°C for 10h and air-baked at 400°C for 4h to obtain a catalyst precursor. Aluminum hydroxide sol was weighed and mixed evenly with the catalyst precursor in a mass ratio of 30:100. Then, 3wt% acetic acid solution and the catalyst precursor mixture were added in a ratio of 100ml:100g, bonded and formed, dried at 100°C for 10h, and then transferred to 500°C air and calcined for 4h to obtain a loaded Fe-Mn activated carbon fiber catalyst.
[0039] Comparative Example 1
[0040] The other conditions are the same as those in Example 4, with the only difference being that in step (1), no iron salt is added to the metal precursor solution.
[0041] Comparative Example 2
[0042] Other conditions are the same as those in Example 4, with the only difference being that in step (1), no manganese salt is added to the metal precursor solution.
[0043] Comparative Example 3
[0044] The other conditions are the same as those in Example 4, except that in step (2), the aging temperature is 60°C.
[0045] Catalyst evaluation process:
[0046] The catalytic reaction of low-concentration VOCs was carried out in a fixed-bed reactor. The initial concentration of VOCs was 400-600 ppm. The carrier gas was air and the reaction space velocity was 12000 h -1 , the reaction temperature is 70-400℃.
[0047] Table 1 is the reaction results of catalyzing low concentration VOCs
[0048]
[0049] From Table 1, it can be seen that the degradation rate of the supported Fe-Mn activated carbon fiber catalyst for 400-600ppm VOCs is above 90%. The catalyst has low cost, high catalytic activity, and good degradation of VOCs at low concentrations. From Comparative Examples 1, 2, and 3, it can be found that the degradation effect of the catalyst on toluene is significantly reduced by changing the preparation conditions.
[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a supported activated carbon fiber catalyst for catalyzing low-concentration VOCs, characterized in that: The preparation method comprises the following steps: (1) washing and drying the carrier activated carbon fiber powder, adding the dried carbon fiber powder to a metal precursor solution and mixing to obtain a mixed solution; the metal precursor is a manganese salt and an iron salt; (2) adjusting the pH value of the mixed solution to 7-10, and then aging, filtering, washing, drying and calcining the mixed solution in sequence to obtain a catalyst precursor; (3) The catalyst precursor and aluminum gel are mixed evenly, bonded and formed by acidification, and then dried and calcined in sequence to obtain a supported Fe-Mn carbon fiber catalyst.
2. The preparation method according to claim 1, characterized in that: In step 1), the activated carbon fiber powder is dried at a temperature of 90-120° C. and for a drying time of 8-12 hours.
3. The preparation method according to claim 1, characterized in that: In step 2), the aging temperature is 15-25° C., and the aging time is 1-5 h; the drying temperature is 90-120° C., and the drying time is 8-12 h; the roasting temperature is 400-600° C., and the roasting time is 1-5 h.
4. The preparation method according to claim 1, characterized in that: In step 3), the aluminum gel is pseudo-boehmite, aluminum dihydrogen phosphate or aluminum hydroxide sol, and the mass ratio of aluminum gel to catalyst precursor is 20-50:100; the acid used for acidification is nitric acid, acetic acid, phosphoric acid, the mass concentration of the acid is 3-10wt%, and the ratio of the amount of acid added to the catalyst precursor mixture is 30-100ml:100g.
5. The preparation method according to claim 1, characterized in that: In step 3), the drying temperature is 90-120° C., and the drying time is 8-12 hours; the roasting temperature is 400-600° C., and the roasting time is 3-5 hours.
6. A supported activated carbon fiber catalyst for catalyzing low-concentration VOCs, characterized in that: The catalyst is prepared by the method described in any one of claims 1 to 5.
7. The supported activated carbon fiber catalyst for catalyzing low-concentration VOCs according to claim 6, characterized in that: Based on the activated carbon fiber carrier, the mass loading of the metal oxide is 5-25%; the iron salt and the manganese salt are any one or more of nitrate, sulfate and chloride, and the molar ratio of Fe:Mn is (1-5):
1.
8. Use of the catalyst prepared according to claim 1 to catalytically degrade VOCs at low concentrations.
9. The use according to claim 8, characterized in that: VOCs include aromatic, ester and hydrocarbon compounds, and the low concentration is 400-600ppm.
10. The use according to claim 9, characterized in that: The carrier gas for the catalytic reaction is air, and the space velocity of the catalytic reaction is 10000-15000h -1 , the reaction temperature is 70-400℃.
Citation Information
Patent Citations
A method for preparing a low-temperature combustion catalyst for toluene and the low-temperature combustion catalyst for toluene
CN108993533B
A method for preparing a manganese-cerium catalyst with high methane catalytic activity and the resulting product.
CN109701547B
Preparation method of supported single-atom dispersed noble metal catalysts
CN111135840B
Zero-valent iron and manganese composite modified activated carbon as well as preparation method and application thereof
CN112934176A
Preparation method of Cu-MnO2 catalyst and application of Cu-MnO2 catalyst in low-temperature catalytic degradation of toluene
CN116212889A
Cited By
Granular active carbon material loaded with ferromanganese bimetallic oxide, preparation method and application of granular active carbon material
CN121016782A